European Union and China in the twenty-first century – problems, opportunities and threats (Economic and Political Thought, 2017)
Today, EU and China – along the US – undoubtedly play a key role inthe international arena. They have established strategic partnership in theirbilateral relations and strive to develop cooperation in all areas. Yet, they alsodissent on many important issues. In this article, I investigate the premisesof EU-China bilateral relations, as well as opportunities and threats to bothparties as far as their status on the global stage is concerned. Moreover,I test the thesis I deem controversial, which claims that the twenty-firstcentury will be Asian century, and de facto the era of China. The literatureon contemporary China, on the role it plays in the international arena and onits relations with the EU is abundant. However no definite answer has beengiven yet as to where China is heading and whether the EU will break up inthe twenty-first century. China’s ‘turn to multilateralism’ is questioned, withsome researchers claiming that it simply serves to conceal China’s long-termgoal, i.e. taking control over the world in the second half of the twenty-firstcentury.